(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The present paper examines the video performance Bibliofagia (2022) by Lian Gaia, an indigenous artist from the Kariri people of Paraíba, whose poetics resonates with indigenous cultural and religious practices, and the debate concerning racial stigmas. By means of this analysis, we intend to unveil the colonial matters underlying territorial and religious conflicts currently occurring in Brazil. We will discuss the political-aesthetic commitment of the performer, whose artistic production aims to challenge religious intolerance and racial violence in Brazil.